2019
DOI: 10.3389/fnbeh.2019.00088
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Bilateral Asymmetry in Electrodermal Activity

Abstract: The Multiple Arousal Theory ( Picard et al., 2016 ) was proposed to explain retrospective observations of bilateral differences in electrodermal activities occurring in threat-related high-stake situations. The theory proposes different cortical and subcortical structures to be involved in the processing of various facets of emotional states. Systematic investigations of this effect are still scarce. This study tested the prediction of bilateral electrodermal effects in a controlled labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…The pre-assessment displays a non-remarkable difference between the biometric data acquired on the two wrists. This condition is also verified by [60]. The asymmetries between skin conductance measurements on the left and the right side is not the key point of this research, but considering the so-structured dataset, it could be considered in future studies.…”
Section: Dataset Attributessupporting
confidence: 55%
“…The pre-assessment displays a non-remarkable difference between the biometric data acquired on the two wrists. This condition is also verified by [60]. The asymmetries between skin conductance measurements on the left and the right side is not the key point of this research, but considering the so-structured dataset, it could be considered in future studies.…”
Section: Dataset Attributessupporting
confidence: 55%
“…Notably, with respect to the electrodermal-effector organ, the contemporary division of ANS function still preserves the idea that the skin receives homogenous sympathetic output signaling the need for motor preparedness (Blakemore and Vuilleumier, 2017; Fredrikson et al, 1998; Le et al, 2019). Yet there is a substantial body of research (e.g., Bjorhei et al, 2019; i Baque et al, 1984; Picard et al, 2016; Richter, 1927) demonstrating that asymmetric ANS responses — as measured by changes in electrodermal activity (EDA) — can differ between right and left body locations. One potential function of such asymmetry could be a limb-specific response to threat directed to one side of the body, challenging the assumption of global homogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In data from wearable electrophysiological recording devices (Ayzenberg and Picard, 2014; Poh et al, 2012; Poh et al, 2010; Sano et al, 2014), collected for the purpose of training computer algorithms to sense, recognize and respond to human emotional information (e.g., el Kaliouby et al, 2006; Picard, 2002; Picard, 2009), asymmetric EDA activity has been observed in response to specific types of emotional situation or arousal (Picard et al, 2016). This work has prompted a secondary resurgence of study on the lateralization of ANS outputs (e.g., Banks et al, 2012; Bjorhei et al, 2019; Kasos et al, 2018; Picard et al, 2016) primarily focused on understanding how data from wearable devices can be used to index biomarkers for mental health monitoring (Arza et al, 2019; Ghandeharioun et al, 2017; Greene et al, 2016; Mohr et al, 2017) and clinical impairment (e.g., autism, Baker et al, 2018; addiction, Carreiro et al, 2015a; Carreiro et al, 2015b; dementia, Kourtis et al, 2019). Stemming from this line of research, the multiple sources of arousal theory (Picard, 2015) points to evidence that asymmetric EDA activation can result from ipsilateral signals from “limbic” regions, in particular the amygdalae, linked to stress or emotional arousal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations